Hubungan Tingkat Pengetahuan Perawatan Kaki Neuropati Otonom Pasien Dengan Kemampuan Perawatan Kaki Neuropati Otonom - Agnes Chyntia S; Nurhayati, Ceria; Imroatul Farida (2024)
Autonomic neuropathy is a complication of diabetes mellitus that affects the autonomic nervous system, causing death. Inappropriate nursing practices are caused by a lack of knowledge about diabetic foot care. This study aims to determine the relationship between level of knowledge and foot care in diabetes patients. This research is analytical research which is included in the Cross Sectional Study. Data analysis in this study used the Spearman Rho Test. because both variables use an ordinal data scale. The data collection tool used in this preliminary study was a questionnaire. The results of the study showed that 41 people (961.2%) had a level of knowledge about autonomic neuropathy foot care, but the majority of respondents' autonomic neuropathy foot care skills were lacking, 47 people (70.1%). There is a significant relationship between the level of knowledge of the patient's autonomic neuropathy foot care and the patient's ability to care for the patient's autonomic neuropathy foot. It is hoped that suggestions for further research can contribute to knowledge, especially for diabetes patients, about managing diabetic foot care, one of which is by increasing the level of knowledge about foot care.